The Influence Of Product Completeness And Product Quality On Purchasing Decisions At Toko Kusen Beton Semoga Jaya - Pramesti, Nabila Ayu; Lestari, Suci Putri; Risana, Dudu (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The purpose of this study was to determine and analyze the effect of product completeness and product quality on purchasing decisions at Toko Kusen Beton Semoga Jaya. The research method used is the survey method, with a sample of consumers with a total of 100 respondents. The data analysis tool used is multiple linear regression using SPSS version 25. Simultaneously product completeness and product quality have a significant effect on purchasing decisions at Toko Kusen Beton Semoga Jaya. Partially product completeness does not have a significant influence on purchasing decisions. Partially product quality has a significant influence on purchasing decisions.